CORPORATE SOCIAL RESPONSIBILITY OF MINING AUTHORITIES OF RANIGANJ COALFIELD IN CONSERVATION OF MINE WATER AND SUPPLY TO LOCAL HABITATS OF DROUGHT PRONE AREAS - GUPTA, ANUP KRISHNA; DATTA, AJOY KUMAR; BASU, RITA (IJRDO - Journal of Business Management, 2018)
Coal, the most important fossil fuel of India, currently meets two-thirds of its energy needs. Though it is least-cost source of primary energy yet mining activities adversely affects the eco-system as a whole. The primary concerns at the regional levels have to do with the environmental impacts on air, water, land, forest, biodiversity and climate. The impact on water is a cause of major concern as it is vital for living things and human life .Growing depletion of ground water table in project areas of Raniganj coalfields warrants immediate steps to restrict drawn down of water table, and conserve source of water both in quantity and quality .As it is a social responsibility of the coal mining authorities to overcome water problems in the region. proper planning on Water Management is important and to meet the objectives implementation of schemes under Corporate Social Responsibility(CSR) by enhancement of knowledge and technology appears major challenge.